2009
DOI: 10.1111/j.1745-4549.2008.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

RHEOLOGICAL AND PHYSICAL PROPERTIES OF LOW FAT CAKES PRODUCED BY ADDITION OF CEREAL Β-Glucan CONCENTRATES

Abstract: This study investigated the effect of replacing shortenings at 20, 30 and 40% levels with two b-glucan concentrates (BGC) prepared from barley and oat on rheological and physical properties of cake batter, and the quality of the resultant cakes as determined by the volume index, texture profile, color of crust, and crumb and staling at three conditions of storage. The consistency, flow behavior indices, storage and loss moduli of batter, increased as the level of BGCs increased. Addition of BGC decreased the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 29 publications
8
58
1
Order By: Relevance
“…Nonetheless, the greater air incorporation and the distribution of this air in the form of fine bubbles generated by the emulsifier may also affect the rheological measurements of the batters. In fact, it has been found that the viscoelastic properties are also dependent on the concentration of air trapped during mixing (Kalinga and Mishra 2009). In this research, G′ and G″ moduli were correlated (p<0.01) to the mean area and the number of bubbles; thus, the smaller the area and the higher the number of the bubbles, the higher the elastic and viscous properties of the batters.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Nonetheless, the greater air incorporation and the distribution of this air in the form of fine bubbles generated by the emulsifier may also affect the rheological measurements of the batters. In fact, it has been found that the viscoelastic properties are also dependent on the concentration of air trapped during mixing (Kalinga and Mishra 2009). In this research, G′ and G″ moduli were correlated (p<0.01) to the mean area and the number of bubbles; thus, the smaller the area and the higher the number of the bubbles, the higher the elastic and viscous properties of the batters.…”
Section: Resultsmentioning
confidence: 53%
“…Most attempts to reduce the fat content of cakes and muffins have focused on their substitution by several carbohydrate fat replacers such as inulin (Rodríguez-García et al 2012Zahn et al 2010), β-glucan (Kalinga and Mishra 2009;Lee et al 2005), cocoa fibre (Martínez-Cervera et al 2011), modified corn starch (Chung et al 2010), and potato maltodextrins, polidextrose or crystalline cellulose (Kamel and Rasper 1988;Khalil 1998). The use of protein fat replacers (Conforti 1998;Psimouli and Oreopoulou 2013) and chia gel (Borneo et al 2010) has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It could be inferred that due to more absorption of water, hardness of dough increases. Kalinga and Mishra (2009) found that batter viscosity for low fat cake increased when shortening was replaced with oat or barley β-glucan concentrates. …”
Section: Resultsmentioning
confidence: 99%
“…Lee and Inglett (2007) reported that oat β-glucan reduces oil uptake of batters during frying, since high water holding capacity and viscosity development have a great effect on the reduction of oil uptake. Kalinga and Mishra (2009) also used β-glucan concentrate as fat replacer for the development of low fat cakes. Therefore, the presented study envisages to incorporate fiber in poories; to reduce the oil uptake while frying, and to study and optimize level of fiber incorporation in accordance with acceptability of the product.…”
Section: Introductionmentioning
confidence: 99%